The management of projects - Morris, Peter W. G. (Thomas Telford, 1994)
Provides a comprehensive survey of the issues involved in initiating, securing, and accomplishing any project. This book also attempts to answer key questions, such as: how did the discipline grow? What do we mean by 'project management'? What lessons have been learned - often painfully?